Time and regional perspectives of food insecurity during the economic crisis in Portugal, 2011-2013 - Gregório, Maria João (2014)
Food insecurity (FI) has received much attention inrecent years, even in high-income countries, due tothe increasing trend of poverty and social inequalitiesindicators, as a result of the global financialcrisis. The establishment of a monitoring system ofFI becomes a priority for food and nutrition policies.Our study aims to evaluate FI trends during theeconomic crisis in Portugal and to identify regionaldisparities throughout the country. Data derivedfrom three surveys conducted by the PortugueseDirectorate-General of Health, concerning FI of thePortuguese population, during the period that Portugalwas under the International Monetary Fundfinancial assistance program (2011-2013). Data werecollected by face-to-face interviews and FI was evaluatedusing a psychometric scale. Logistic regressionmodels were used to identify regional disparities inFI. The prevalence of FI was relatively unchangedat national and regional levels, during the analysisperiod. Data from 2013 indicates a high prevalenceof FI (50.7%), including 33.4% for low FI, 10.1% formoderate FI and 7.2% for severe FI. Disparities accordinghealth region were also found for household FI.Algarve, Lisboa and Vale do Tejo were the two regionswith the highest levels of FI, even after controllingfor other socioeconomic variables. High levels of FIfound in Portugal and the different regional profilessuggest the need for regional strategies, in particularin the most affected regions based on a broaderaction with different policy sectors (health, socialsecurity, municipalities and local institutions inthe field of social economy).